Ate, Senador, Pilipino: A Critical Discourse Analysis of Kinship and Moral Authority in a Contemporary Philippine Political Speech - Leonardo Daquioag Tejano (IKAT: The Indonesian Journal of Southeast Asian Studies, 2026)
This paper conducts a critical discourse analysis of Senator Imee Marcos's speech delivered on November 17, 2025, at an anti-corruption rally at a Christian religious organization, Luneta Park, Manila. The speech publicly accused her brother, President Ferdinand "Bongbong" Marcos Jr., of long-term drug addiction, marking a decisive rupture in Philippine elite politics. Employing Fairclough's three-dimensional Critical Discourse Analysis (CDA) framework, the study examines how kinship is mobilized to construct moral authority, how the speaker navigates the boundary between private grief and public accountability, and what ideological work is performed by the identity labels "Ate," "Senador," and "Pilipino." The speech is treated in this study as a documented public event whose transcript was derived from video footage verified through multiple independent media sources, including the full recording published by ANC 24/7 on YouTube. The analysis reveals that the speech is a meticulously crafted discursive performance in which the ate (elder sister) role functions as a culturally embedded source of moral legitimacy, enabling the speaker to reframe a political attack as a familial intervention grounded in utang na loob, kapwa, and loob. The findings demonstrate that the speaker's oscillation between private grief and public duty is not rhetorical inconsistency but a deliberate strategy that depoliticizes the accusation while amplifying its moral force. The paper argues that the speech performs significant ideological work by recasting a crisis of political legitimacy as a crisis of familial and moral decay, thereby challenging presidential authority on culturally resonant grounds. Implications for applied linguistics, political communication, and Philippine studies are discussed.